Antibacterial Activity of Streptococcus mutans from Saga Herbaceous Plant (Abrus precatorius): In Silico Study - Richa Mardianingrum; Neta Ekayanti Suganda; Srie Rezeki Nur Endah; Ruswanto Ruswanto (ALCHEMY Jurnal Penelitian Kimia, 2023)
Antibacterial is a substance that can inhibit growth or can even kill bacteria that cause infection. One of them is infection with Streptococcus mutans bacteria that cause damage to teeth, such as dental caries. Dental caries is a disease that affects many adults and children, permanently damaging the tooth layer and forming small holes in the teeth. The purpose of this study was to find active compounds from the herb Saga plant (Abrus precatorius), which has the potential to be antibacterial of S. mutans in silico. The methods used are pharmacokinetics and toxicity screening, Lipinski's Rule of Five, as well as simulations of molecular docking and molecular dynamics. The Abruquinone D (-6.43) and Abruquinone F (-7.08) were predicted to have stable interactions and be similar to amoxicillin (-7.69) and native ligand (-8.56 kcal/mol) based on the results of screening and molecular docking simulations of active compounds from Saga herbaceous (Abrus precatorius) against deoxycytidylate deaminase receptors. Molecular dynamics findings confirmed by MMGBSA methods that Abruquinone D (-41.3876 kcal/mol) had a lower energy value than Abruquinone F (-24.8521 kcal/mol). It can be inferred that Abruquinone D has a higher potential as an antibiotic (S. mutans) than Abruquinone F.